Development of items in Acid-Base Identification Experiments Using Natural Materials: Validity Test with Rasch Model Analysis - Sri Mulyanti; Wati Sukmawati; Nur Elisa Hawa Tarkin (Phenomenon : Jurnal Pendidikan MIPA, 2022)
The development of the test in the form of multiple choice items as 18 questions, aims to measure students' abilities in the experiment of identifying acid-base compounds with natural indicators. The study used descriptive quantitative methods. 79 high school students who have studied acid-base experiment with natural indicators, as the subject of validity test. Validity analyzed by Rasch model in the Winsteps program, including the level of problem difficulty, item validity, construct validity, content validity, and instrument reliability. The results obtained are evenly distributed, so that it can measure students' abilities at various levels of knowledge. Construct validity is evidenced by the raw variance value of 31%, and content validity shows that the questions fit the Rasch model. The feasibility of the instrument can also be seen from its very good reliability value of 0.91. The developed test can be used as a measuring tool for the success of acid-base identification practicum with natural indicators, which have been developed in various researches on the development of environmentally friendly acid-base practicums from natural materials.